Optogenetic approaches for functional mouse brain mapping - Lim, Diana H.; LeDue, Jeffrey; Mohajerani, Majid H.; Vanni, Matthieu P.; Murphy, Timothy H. (Frontiers in Neuroscience, 2013)
To better understand the connectivity of the brain, it is important to map both structural and functional connections between neurons and cortical regions. In recent years, a set of optogenetic tools have been developed that permit selective manipulation and investigation of neural systems. These tools have enabled the mapping of functional connections between stimulated cortical targets and other brain regions. Advantages of the approach include the ability to arbitrarily stimulate brain regions that express opsins, allowing for brain mapping independent of behavior or sensory processing. The ability of opsins to be rapidly and locally activated allows for investigation of connectivity with spatial resolution on the order of single neurons and temporal resolution on the order of milliseconds. Optogenetic methods for functional mapping have been applied in experiments ranging from in vitro investigation of microcircuits, to in vivo probing of inter-regional cortical connections, to examination of global connections within the whole brain. We review recently developed functional mapping methods that use optogenetic single point stimulation in the rodent brain and employ cellular electrophysiology, evoked motor movements, voltage sensitive dyes, calcium indicators, or functional magnetic resonance imaging to assess activity. In particular we highlight results using red-shifted organic voltage sensitive dyes that permit high temporal resolution imaging in a manner spectrally-separated from Channelrhodopsin-2 activation. Voltage sensitive dye maps stimulated by Channelrhodopsin-2 were dependent on intracortical synaptic activity and were able to reflect circuits used for sensory processing. Although the methods reviewed are powerful, challenges remain with respect to finding approaches that permit selective high-temporal resolution assessment of stimulated activity in animals that can be followed longitudinally.